WRITING STYLES SPECIFIC TO MANUSCRIPTS - Gulinur Xamidova, daughter of Alisher; Baisov Ahmad Sobirjonovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article provides detailed information about writing and its evolution. Various types of writing are analyzed during its developmental stages. It proves the significant importance of writing in our daily lives and linguistic studies. Additionally, types of writing are illustrated with examples and their usage scenarios are examined.